Individual differences and personal social network size and structure - Roberts, S; Wilson, R; Fedurek, P; Dunbar, R (2008)
Although personality factors are known to influence sociality, there is as yet no evidence to suggest that they directly affect the size of social networks. In the present study, 168 adults completed questionnaires on social network size (focussing on the two inner, most intimate layers of the network: support clique and sympathy group) and the personality sub-scales for extraversion and neuroticism from the Eysenck Personality Inventory (EPI). There was a significant gender-bias in contacts at both levels (suggesting a degree of sexual social segregation). Extraversion was correlated with the size of support clique, but not the size of the sympathy group. However, age correlated with extraversion score, and when age was controlled for, there was no significant correlation between extraversion and the size of either the support clique or sympathy group. There was also no correlation between neuroticism and the size of support clique and sympathy group. These results suggest, when a wide range of ages are included in the sample, the relationship between personality and network size is more complex than previous studies have shown. © 2007 Elsevier Ltd. All rights reserved.